Recoding: Expansion of Decoding Rules Enriches Gene Expression - Atkins, John F.; Gesteland, Raymond F. (Nucleic Acids and Molecular Biology,, 2010)
The dynamic nature of decoding the information in messenger RNA was unanticipated at the time the genetic code was first deciphered. We now know that both the meaning of individual codons and the framing of the readout process can be modified by information in specific messenger RNAs. This book describes this "Recoding" phenomenon, revealing the diversity of an additional layer of information in mRNAs that serves to enrich the expression of genes. Knowledge of recoding is essential for understanding the organization and expression of genes in viruses and all organisms ranging from bacteria to archeae to plants to humans, making Recoding pertinent to all biological sciences.